PENGARUH DEWAN KOMISARIS TERHADAP ENVIRONMENTAL DISCLOSURE PADA PERUSAHAAN MANUFAKTUR YANG LISTING DI BEI TAHUN 2015-2017 - Juhairiyah Juhairiyah; Afifudin Afifudin; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
BSTRACTThis study aims to determine the influence of the Board of Commissionerson the Environmental Disclosure of Manufacturing Companies Listing on theStock Exchange in 2015-2017. The data used in this study is secondary data, thepopulation of this study were 150 manufacturing companies listing on the StockExchange in 2015-2017 and the total sample of 39 companies through purposivesampling method. The results of this study indicate that partially the size of theboard of commissioners, the proportion of independent board of commissionersand the number of board of commissioners meetings have no effect onenvironmental disclosure, while the educational background of the board ofdirectors affects environmental disclosure.Keywords: Board of Commissioners Size, Proportion of Independent Board ofCommissioners, Board of Commissioners' Educational Background,Number of Board of Commissioners Meetings and EnvironmentalDisclosure